Unusual magnetic damping effect in a silver-cobalt ferrite hetero nano-system - Sharma, Surender K.; Vargas, Jose Marcelo; Vargas, Nicolás Manuel; Castillo Sepúlveda, Sebastián; Altbir Drullinsky, Dora Rosa; Kleber, Roberto Pirota; Zboril, Radek; Zoppellaro, Giorgio; Knobel, Marcelo (Royal Society of Chemistry, 2015)
Fil: Sharma, Surender K.. Universidade Estadual de Campinas; Brasil. Université Paris Diderot - Paris 7; Francia. Palacký University Olomouc; República Checa